Lasem Heritage Center( Pendekatan Pada Arsitektur Etnik Kontemporer ) - Pramono, Esnan, Dr. Ir. Dhani Mutiari, MT (2016)
Lasem is a city placed in the Javanese north coast littoral which is rich with its kinds of cultures and ethnics. The multicultural societies gives impact on its various cultures due to crosscultural itself, therefore Lasem City has its various culture, heritage, Art and Architecture. But on its proggress in Lasem City, it hasn't shown the proggress for the management of the potency itself. The Potency of Lasem City as heritage area is high, due to the the proof that the data collection has been done by the program of structuring and preserving the relic city (P3KP) Regency of Rembang that it has been found some cultural heritages. While the program of Rembang Regency Government in RUTRK has already published managing the city of Lasem as the area of cultural heritage, as well as the communities in Lasem who also launched Lasem city as relic city. Based on the cases and potency of Lasem city, therefore it needs management for the potency existed in Lasem city. The management itself should be based on the principles of conservation building planning and it involes the societies around for the management system. The condition of the pluralistic societies also become the considerations in order that the conflict in managing will not happen therefore it needs solutive planning and designing in developing the area itself. One of the analysis and concept to develop and introduce the city of lasem is by creating the Lasem Heritage Center Planning namely the cultural heritage centre which accomodate the cultural legacy and the history of Lasem city where the management involves communities exist in Lasem. The Building design concept style contemporary ethnic namely with the purpose to raise traditional etnic arhitect in Lasem in the modern design.